Association between Metabolic Score for Visceral Fat and the risk of hypertension in different ethnic groups: a prospective cohort study in Southwest China - Zhang, Fuyan; Wang, Yiying; Zhou, Jie; Yu, Lisha; Wang, Ziyun; Liu, Tao; Yu, Yangwen (Frontiers in Endocrinology, 2024)
Objective: Visceral adipose tissue assessment holds significant importance in hypertension prevention. This study aimed to explore the association between the Metabolic Score for Visceral Fat (METS-VF), a new indicator based on laboratory and anthropometry measures, and hypertension risk and to further investigate the association between the METS-VF and the risk of hypertension in different ethnic groups.Methods: In this study, a total of 9280 people from 48 townships in 12 districts (counties) of Guizhou Province were selected for the survey using a multi-stage cluster random sampling method, and 5127 cases were finally included in the analysis after excluding those with missing relevant data, losing visits, dying at follow-up, those who suffered from hypertension at baseline, and those whose information on the outcome of hypertension was not clear. Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) between METS-VF and incident hypertension, and accelerated failure time (AFT) model was applied to analyze the association between METS-VF and the onset time of hypertension.The total person-years (PYs) of the 5127 subjects were 36,188.52 years, and the median follow-up time was 6.64 years. During follow-up, 1127 patients were newly diagnosed with hypertension and the incidence density was 31.14/1000 PYs. After adjusting for multi-variables, ， 删除[乍惊乍喜]: This study aimed to 删除[乍惊乍喜]: metabolic score of visceral fat ( 删除[乍惊乍喜]: ) 删除[乍惊乍喜]: 删除[乍惊乍喜]: analysis 删除[乍惊乍喜]: variate 删除[乍惊乍喜]: compared with the METS-VF first (Q1), the third (Q3) and fourth (Q4) groups of the METS-VF increased by 29. 9% and 61.5%, respectively [HR=1.299(1.061, 1.590) and 1.615(1.280, 2.036)]. The risk of hypertension increased with higher 1.500), Ptrend<0.001].In the Han Chinese population, Q2 and Q3 increased the risk of hypertension in the Han population [HR=1. 459 (1.111, 1.917), 1.999 (1.417, 2.718)], and the onset of hypertension was advanced by 0.653 [β=-0.653(-0.930,-0.375)] years for per 1 unit increase in METS-VF. However, these associations were not found in ethnic minorities.METS-VF was significantly positively associated with the risk of hypertension, and the association was different among ethnic groups.